Distribution of Trace Metals in Street Dusts and Tree Leaves and Their Source Identification in a Mid-Populated Anatolian City - Nuhoglu, Yasar; Yazici, Mustafa; Nuhoglu, Cigdem; Kuzu, S. Levent; Osmanhoglu, Ahmet E.; Kam, Erol (SPRINGER, 2020)
Sivas is a central Anatolian city in Turkey with mid-population. Due to its geographical structure high air pollution episodes can be observed in the atmosphere of Sivas. A study with city wide sampling campaign can help to identify the possible sources. Therefore, we aimed to investigate the multi-elemental and multi-point analysis of trace metals in street dusts and tree leaves in Sivas. In the street dusts, Ca concentration was > 10%. Fe, Cl, and K contribution was 2.5%, 1.75%, and 1.1%, respectively. The average S and Ti concentrations were between 1 and 10 mg/g, I, Mn, Sr, Cr, V, Ba, Zn, Ni, Zr, and Cu were between 1 and 0.1 mg/g, and W, Pb, Sn, Th, Rb, Sb, Co, Bi, As, U were between 0.1 and 0.01 mg/g, in the ascending order. The same elements were investigated for vegetation. Ca, K, S, and Cl were the elements with highest contribution.
Keywords: Street dust; Leaf; Trace metal; Source identification; PCA; ROAD DUST; HEAVY-METALS; SCOTS PINE; POLLUTION; CADMIUM; POLLUTANTS; TOXICITY; AREAS; CHINA; PM2.5; Environmental Sciences & Ecology; Toxicology